PENGOLAHAN AIR LIMBAH INDUSTRI : PREPARASI DAN KARAKTERISASI KOPOLIMER CANGKOK ASAM AKRILAT PADA FILM HDPE - Yohan, Yohan; Nur, Rifaid M.; Hendrajaya, Lilik; Siraj, E. S. (E-Journal Widya Kesehatan dan Lingkungan, 2005)
Grafting pre-irradiation process of styrene monomer on high desity poluethylene (HDPE) film for hydrophilic membrane as membrane of cationic exchanger have been done. HDPE film is irradiated by y-ray then grafted by acrylic acid monomer in water. The preparation conditions at which the optimum grafting process are determined, such as rate and total dose of irradiation, monomer concentration, time and temperature of grafting. Characterization of some properties of the prepared grafted membranes were studied and accordingly the possibility of its practical use in fuel cell and in waste water treatment from toxic heavy metals, such as As, Cd, Co, Cu, Fe and Pb was investigated. Good relative condition to graft was using total dose of 45 kGy, dose rate was 7 kGy/hour, acrylic acid was 40% volume, grafting time was 90 minutes, and grafting temperature was 70oC gave percent of grafting HDPE-g-AA = 800-900% weight. The chelated metal ions were easily desorbed by treating the membrane with 0.1N HCl for 2 hours at room temperature. Finally, a mixture of there metals in the same feed solution was used to determine the selectivity of the membrane toward different metals. The results obtained for the prepared membranes showed a promise for their applicability in the removal of heavy metals from industrial wastewater.